KONSTITUSIONALITAS JABATAN WAKIL MENTERI PERSPEKTIF SIYASAH DUSTURIYAH - Firmansyah; Samin, Sabri; Mustarin, Basyirah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
The appointment of deputy ministers is the president's prerogative which aims to assist ministers in carrying out ministerial affairs in certain ministries. This study aims to find out how urgent the appointment of deputy ministers in Indonesia is and how the legitimacy of the appointment of deputy ministers is in the view of siyasa dusturiyah. The problem in this research is in Article 10 of law number 39 of 2008 concerning state ministries as the legality of appointing deputy ministers in the phrase